2016
DOI: 10.1097/pgp.0000000000000255
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Spectrum of MED12 Exon 2 Mutations in Multiple Versus Solitary Uterine Leiomyomas From Russian Patients

Abstract: Uterine leiomyomas (ULs) are common benign tumors affecting women of different ethnicities. A large proportion of UL has mutations in MED12. Multiple and solitary ULs usually manifest with different severities, suggesting that their origin and growth pattern may be driven by different molecular mechanisms. Here, we compared the frequency and the spectrum of MED12 exon 2 mutations between multiple (n=82) and solitary (n=40) ULs from Russian patients. Overall, we detected MED12 exon 2 mutations in 51.6% (63/122)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Two prior studies have explored the association between MED12- mutation status and tumour location with negative results, possibly due to different study settings and smaller sample sizes 18, 24 . Brosens et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two prior studies have explored the association between MED12- mutation status and tumour location with negative results, possibly due to different study settings and smaller sample sizes 18, 24 . Brosens et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MED12 mutations are associated with smaller tumour size and larger number of tumours within the uterus, and they are less frequent in histopathological leiomyoma variants 16, 17, 2023, 25, 27 . Earlier studies, with limited sample sizes, have failed to detect underlying associations between other clinical factors and MED12 -mutation status, however 17, 18, 20, 22, 24 . To scrutinise these associations further, we have prospectively collected a series of 763 leiomyomas from 244 hysterectomy patients with comprehensive clinical data.…”
Section: Introductionmentioning
confidence: 95%
“…MED12 encodes a part of the mediator multiprotein complex, which regulates gene expression by linking transcription factors and RNA polymerase II 32. The association of positive MED12 mutation status with larger number of fibroids has been mentioned by Heinonen et al 18 and reported in detail in our previous study comparing multiple and solitary ULs 19. Considering these data and elevated rate of the COMT Val/Val genotype in the patients with multiple ULs detected in the present study, we have checked whether the COMT Val158Met polymorphism is associated with MED12 exon 2 mutations in tumours.…”
Section: Discussionmentioning
confidence: 69%
“…Finally, considering the increased rate of COMT Val/Val genotype in the patients with multiple ULs and reported previously association of MED12 exon 2 mutations with multiple fibroids,18 19 we analysed whether the COMT Val158Met polymorphism is linked to the presence of MED12 exon 2 mutations in tumours. A total of 118 tumours (26 solitary+92 multiple) were screened for somatic MED12 exon 2 mutations.…”
Section: Resultsmentioning
confidence: 99%
“…Recent data suggest that both pathways may account for a considerable percentage of UL rearrangements of high mobility group protein gene 2 (HMGA2) and, much more frequently, those affecting MED12. Apparently, both mutations do not overlap with each other [Bertsch et al 2014] and seem to be associated with different tumor sizes [Ono et al 2012] as well as with their presence as multiple versus solitary tumors Osinovskaya et al 2015]. Tumors with HMGA2-rearrangements are less frequent than their MED12-mutated counterparts [Makinen et al 2013] and preferentially occur in larger, solitary lesions [Holzmann et al 2014].…”
Section: Gene Interactions: Ulmentioning
confidence: 99%